Ghrelin the novel hormone - Abdul Rahim, Roslina (IIUM Press, International Islamic University Malaysia, 2017)
Previous study has shown 24-hours diurnal rhythm of ghrelin secretion in human but not in rats. Thus, the first objective of this study is to determine the variation in secretion of ghrelin hormone during active phase in rats. Male Sprague Dawley rats with 250-300 g of body weight were used and all experimental rats were placed in a reversed cycle room for 2 weeks. After reversed cycle, blood samples were collected through cardiac puncture every two consecutive hours from 8 p.m. to 8 a.m. Ghrelin hormonal assay was done on each blood samples. The highest and the lowest point of ghrelin secretion were determined. The result showed that at 12 a.m. ghrelin is at the lowest and the highest at 2 a.m. The lowest time of ghrelin secretion was used as the starting point in phase 2, where the effects of ghrelin given in different concentration (1 & 10 μg/kg) on plasma arginine vasopressin (AVP), aldosterone, Na+, K+, Cl- and total protein (TP) were determine. Previous studies have showed that ghrelin given centrally (1 pmol/rat) or systemically (1 & 10 nmol/rat) causes release in AVP and aldosterone indirectly, but no changes were determined in plasma Na+ and TP. Ghrelin was introduced intravenously via the lateral vein of rat’s tail. Blood samples were collected at 0 min followed by 15, 30, 45 and 60 min after the injection. Ghrelin caused release in aldosterone and AVP in both concentrations. Plasma Na+ increased significantly in both concentrations compared to control group. Plasma Cl- only increased significantly when given in 10 μg/kg of ghrelin. Meanwhile, plasma K+ and TP decreased significantly in both concentration compared to control group but within the normal range. In conclusion, ghrelin produced changes in plasma osmolality indirectly.